Antihyperlipidemic activity of petroselinum crispum seeds in high fat diet induced atherosclerosis in experimental animals (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Atherosclerosis is one of the major contributing factors for the mortality due to cardiovascular diseases. Although a number of therapeutic agents are available still the management of atherosclerosis is not completely possible due to associated side effects with these therapeutic agents. Due to this herbal drug are considered as alternative for the treatment of atherosclerosis. Among these herbal drugs, Petroselinum crispum seeds are considered as potential agent for the treatment of atherosclerosis. In the present study, hydroalcoholic extract and petroleum ether extract of P. crispum seeds was prepared and anti-atherosclerotic activity was evaluated in High fat diet induced atherosclerosis in rats. Qualitative and quantitative analysis of hydroalcoholic extract was carried and in vitro and in vivo antioxidant activity was evaluated. Antiatherosclerotic activity was evaluated by measuring serum cholesterol, serum triglycerides, serum low-density lipoprotein (LDL), very low-density lipoprotein (LDL) and high-density lipoprotein (HDL) level in animals. Animals were kept on high fat diet for 45 days and different doses of hydroalcoholic and petroleum ether extract were administered. Administration of different doses significantly attenuated the elevated level of serum cholesterol, serum triglycerides, serum LDL, VLDL and elevated HDL level. Oxidative stress was also found to be significantly attenuated in in vitro and in vivo models. From the study it can be concluded that hydroalcoholic and petroleum ether extract of P. crispum seeds significantly attenuated elevated oxidative stress and lipid profile.